Does Psychological Contract Fulfillment Mediate the Relationship Between Organizational Culture and Affective Commitment? Leader-Member Exchange as Moderator - Khawaja Jehanzeb; Nadeem Ahmed Bashir (SAGE Open)
The purpose of this study is to observe the effect of perceived organizational culture on affective commitment. The study also examines the mediating role of perceived psychological contract fulfillment (PPCF) and the moderating role of leader-member exchange (LMX). Using a stratified sampling technique, data were obtained from 297 workers employed in a telecommunications sector located in the capital city of Riyadh, Saudi Arabia. To test the developed hypotheses, structural equation modeling was performed using AMOS 21.0. The results indicated that perceived organizational culture has a significant impact on PPCF and affective commitment. They also showed that PPCF partially mediates the relationship between perceived organizational culture and affective commitment. Furthermore, LMX moderates these relationships. The results of this study are valuable for the telecommunications sector and strategic decision-makers who seek to enhance affective commitment among their employees. Moreover, this study provides opportunities for researchers and scholars to conduct further research in this area. This study helps address inconsistent findings in previous research on perceived organizational culture, PPCF, and affective commitment. Furthermore, it makes a novel contribution by identifying LMX as a fundamental mechanism linking perceived organizational culture and PPCF, particularly in the context of Saudi Arabia.